(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the coverage of the Uzbek agricultural profession in historical sources of different periods. In particular, the description of the planting of crops, its significance and the promised quarry are revealed in the Avesta, the oldest written source on the history of Turan. In addition, there are traces of the agricultural system of the early Middle Ages in culture and reflection in the worldview. At the same time, based on sources, the position of the population engaged in agriculture in subsequent historical periods in society and the state is shown.